Polyurethane foam materials and their industrial applications - Ates, Murat; Karadag, Selin; Eker, Aysegul Akdogan; Eker, Bulent (WILEY, 2022)
In this review article, polyurethane (PU) foam materials are presented in various industrial applications. PU foams have started to replace metals and plastics in various engineering applications by combining the hardness and durability of metal with the flexibility of rubber. PU foams can be synthesized with various isocyanates, polyols, chain extenders and crosslinkers to serve many specific applications, such as bio-based composite foam, flexible hard/soft PU foam, polymer foam etc. There are different factors to change of hard and soft segments of PUs. These changes form different products, such as urethane, biurets, allophanates and isocyamurates, etc. This review article mostly concentrates on the basic chemistry of the building blocks of PUs and recent developments in industrial applications of PU foams, such as insulator material, sound insulators, refrigerator and freezing insulators, furniture, shoes, automotive materials, coatings and adhesives and other applications. (c) 2022 Society of Industrial Chemistry.
Keywords: flexible PU foam; hard; soft PU foam; open cell foam; crosslink density; polymer foam; bio-based composite foam; IN-VIVO BIOCOMPATIBILITY; PHASE-CHANGE MATERIALS; MECHANICAL-PROPERTIES; THERMOPLASTIC POLYURETHANE; THERMAL-DEGRADATION; COMPOSITE FOAMS; BLOWING AGENTS; CARBON-DIOXIDE; KRAFT LIGNIN; PERFORMANCE; Polymer Science